Acute echocardiographic effects of sotalol on ventricular systolic function in dogs with ventricular arrhythmias. (3rd July 2018) - Visser, Lance C.; Kaplan, Joanna L.; Nishimura, Satoko; Gunther‐Harrington, Catherine T.; Bélanger, Catherine; Oldach, Maureen S.; Stern, Joshua A.; Mueller, Mikaela S.
Abstract : Background: Sotalol is a commonly used antiarrhythmic drug that may alter ventricular function. Objective: To determine the effect of sotalol on echocardiographic indices of ventricular systolic function in dogs with ventricular arrhythmias. Animals: Thirty‐five client‐owned dogs with ventricular arrhythmias. Methods: Dogs with ventricular arrhythmias (n = 27) had an echocardiogram and 5‐minute ECG performed at baseline and 2‐4 hours post‐sotalol (2‐2.5 mg/kg PO once). Eight additional dogs underwent the same protocol but did not receive sotalol (within‐day variability controls). Left ventricular (LV) internal dimension at end‐systole normalized to bodyweight (LVIDs_N), LV ejection fraction (LV EF), LV shortening area, LV fractional shortening, tricuspid annular plane systolic excursion (TAPSE), and right ventricular systolic myocardial velocity were evaluated as indices of systolic function. Results: All indices except TAPSE had mild decreases in systolic function post‐sotalol (all P  ≤ .0007) compared with baseline but only the percent change in LVIDs_N and LV EF were significantly ( P  ≤ .0079) different from the percent change of the same indices in control dogs. Sinus heart rate, ventricular premature complexes/5‐minutes, and arrhythmia grade also were decreased post‐sotalol (all P  ≤ .01) compared with baseline when assessed by a 5‐minutes ECG. No dog experienced an adverse event post‐sotalol, including dogs with systolic dysfunction or atrial enlargement. Conclusions and Clinical Importance: A single dose of sotalol may cause a mild decrease in LV systolic function in dogs with ventricular arrhythmias. Sotalol appears to be well tolerated, even in dogs with atrial enlargement or systolic dysfunction.